EXPLORING SOCIAL SUBJECTIVITY IN DORIS LESSING’S AFRICAN STORIES - Hooda, Chanchal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Doris Lessing’s African Stories provide a compelling exploration of the intersections between individual consciousness and the larger socio-political realities of colonial and postcolonial Africa. This study investigates the concept of social subjectivity in her African narratives, focusing on how characters’ identities are shaped, negotiated, and often fractured within complex structures of race, class, gender, and power. Lessing’s stories not only foreground personal experiences but also reflect the tensions of colonial domination, cultural displacement, and the struggle for selfhood in oppressive social contexts. Through an ecocritical and postcolonial lens, this research examines how Lessing’s characters embody the contradictions of belonging and alienation. The landscapes of Africa, described with both intimacy and estrangement, serve as a backdrop for examining the dynamics of social relations and individual subjectivity. Lessing’s portrayal of African and European characters highlights the entangled realities of colonial encounter—where identity becomes inseparable from historical and cultural forces. By engaging with themes of authority, marginality, and resistance, this work argues that Lessing’s African Stories move beyond personal narratives to interrogate broader questions of social justice, identity formation, and cultural hybridity. Ultimately, the study reveals how Lessing situates subjectivity not as an isolated psychological condition but as a phenomenon deeply embedded in the social and political fabric of African life under colonial rule.